Dental Unit Management System with a Web Application - Wongkamhang, Anantasak; Nirapai, Anuchit; Thongpance, Nuntachai; Imura, Pariwat; Chotikunnan, Phichitphon; Roongprasert, Kittipan (International Journal of Online and Biomedical Engineering (iJOE), 2025)
The study developed a web-based dental unit management system (DUMS) to overcome inefficiencies, high maintenance costs, and delays caused by traditional manual practices in dental clinics. The system integrates a relational database, role-based access control (RBAC), and IoT technologies to provide secure, real-time monitoring and predictive maintenance of dental equipment. Following the system development life cycle (SDLC), four user roles— client, engineer, administrator, and factory—were defined, along with essential modules for information management. Reliability was validated through unit testing, integration, user acceptance testing (UAT), and load testing. Results confirmed continuous data synchronization, secure role-based access, and stable performance under high demand. Internet of Things (IoT) integration enables predictive scheduling, early anomaly detection, and real-time tracking of operational parameters. Overall, DUMS enhances efficiency, equipment availability, and patient-centered care while aligning with Industry 4.0 healthcare digitization and contributing to research on IoT-enabled healthcare systems.